Comparing different lymphatic filariasis patient estimate approaches and results in Ethiopia - Mengistu, Belete; Kebede, Fikreab; Negash, Biruck Kebede; Miheret, Addisalem; Beyene, Biruk Kebede; Abetew, Solomon; Tedla, Berihu Gebremariam; Oucha, Asfaw Kejella; Alene, Shigute; Backers, Sharone; Burgert, Clara; Toubali, Emily; et al. (Frontiers in Tropical Diseases, 2024)
Background The World Health Organization (WHO) recommends that countries ensure morbidity management and disability prevention (MMDP) services are available to all lymphedema and hydrocele patients in lymphatic filariasis (LF)-endemic areas. The first step in ensuring the availability of MMDP services is to understand the number and distribution of people with lymphedema and hydrocele. We examined the burden of lymphoedema and hydrocoele using different patient estimation approaches employed in endemic districts of the Beneshangul-Gumuz and Tigray regions of Ethiopia. Methodology/principal findings In Approach I, trained health extension workers (HEWs) conducted the patient estimates during a door-to-door pre-mass drug administration (MDA) census. Validation of a sample of the data collected was integrated with a post-MDA coverage survey. In Approach II, trained HEWs conducted a stand-alone patient estimation, and clinical officers validated all suspected patients. In 15 districts, 753,557 individuals were surveyed. A total of 1,645 lymphedema (1:1.6 male-to-female ratio) and 517 hydrocele cases were identified. The prevalence of lymphedema and hydrocele was 40 per 10,000 in the adult population and 25 per 10,000 in the adult male population, with wide variation across districts. Validation in Approach I showed that 94% of the lymphedema cases and 77% of hydrocele cases were correctly identified by the HEWs, while 60% and 53% were correctly identified in Approach II. Conclusion/significance Patient estimation is important for planning, prioritization, targeting interventions, and monitoring progress in LF-endemic areas. Trained HEWs can correctly identify most cases using a standardized patient estimate job aid and questionnaire, even when cascade training is used. For the purposes of LF elimination, these results are sufficient and at a low cost per district. Ethiopia’s LF program could integrate patient estimations into MDA activities in the remaining LF-endemic districts with minimal cost and effort.